Left atrial myxomas in childhood: Presentation with emboli—diagnosis by ultrasonics - Pridie, Ronald B. (1972)
Three children with left atrial myxomas are described. All suffered major arterial occlusion with consequent permanent morbidity before the diagnosis was made and the tumour removed. Each child had had previous small embolic phenomena. In two, the diagnosis was made by ultrasound. In any child who has had an arterial embolus without obvious cause, a left atrial myxoma should be considered and looked for by an ultrasonic mitral echogram.